A spatially and functionally distinct pool of TORC1 defines signaling endosomes in yeast. Issue 5 (4th May 2019) - Hatakeyama, Riko; De Virgilio, Claudio
ABSTRACT: The evolutionarily conserved target of rapamycin complex 1 (TORC1) regulates cell growth in a homeostatic manner by tuning anabolic and catabolic processes in response to nutritional and hormonal cues. Interestingly, rather than being localized at the plasma membrane as perhaps expected for an integrator of extracellular signals, TORC1 mainly localizes at vacuolar (in yeast) and lysosomal (in more complex eukaryotes) membranes where it seems optimally placed to sense both the nutrient status within the cytoplasm and the vacuolar/lysosomal compartment. How TORC1 controls downstream targets that are distant from the vacuole/lysosome, is currently poorly understood. In this context, we recently identified and characterized 2 spatially and functionally distinct pools of TORC1 in the budding yeast Saccharomyces cerevisiae : one at the vacuole that promotes protein synthesis, and another one at endosomes that inhibits protein degradation. Thus, our findings highlight the presence of spatially separated pools of TORC1 that are commissioned with functionally specific tasks within cells. In addition, they pinpoint the existence of signaling endosomes in yeast, which raises numerous new questions that are warranted to direct future research in this area.